(untitled) (Bangladesh Journal of Medical Science, 2015)
The growing geriatric population should be given a chance to fulfill their late age in the best way possible, including those affected with head and neck malignancies. This report describes about a 76 year old man with squamous cell carcinoma of tongue managed with the typical cancer treatment modes and shown a good outcome. Bangladesh Journal of Medical Science Vol.14(4) 2015 p.413-416